Sodelovanje kriminalistov s centri za socialno delo - Gorenak, Irena (Socialno delo, 2007)
The author presents a research of the cooperation and relations btween criminal investigators and workers at the centres of social work. Upon the assessment of interpersonal competences of the former and the assessment of their communication styles in their contacts with the latter, she calculates the impact of these two factors on the cooperation and relationships between the two groups. The project included 117 workers at the centres of social work(not only social workers). The main finding is that both factors do indeedhave an impact. Interpersonal competences of criminal investigators accounted for 19.9%, and their communication styles for 8.2% of the variance of cooperation and relationships
Keywords: kriminalisti; centri za socialno delo; sodelovanje; komunikacijski slogi